In-Formality in Access to Housing for Latin American Migrants: A Case Study of an Intermediate Chilean City - Gonzalez-Lagos, R (Routledge, 2019)
Antofagasta is an intermediate Chilean city featuring an extractive mining sector which attracts a population of low-income migrants, internal and cross-national, looking for economic opportunities. This leads to a gap between supply and demand for rental housing, subletting and homeownership, resulting in a highly speculative housing market. This paper examines the consequent increase in so-called informal settlements and shows how self-built housing has become an alternative way for the population of internal and foreign migrants to access housing. Drawing upon both quantitative (secondary statistics and a survey with 102 households) and qualitative research (15 in-depth interviews), the paper shows how a private-led, profit-oriented and racist housing market has consolidated in the city. Moreover, by shedding light on the everyday ways in which residents access urban services, the research points to the complex forms of juxtaposition between the formal and the informal in central, peri-central and peripheral sectors of the city. Therefore, the paper questions the formal–informal dualities in access to housing and the necessity to rethink housing and urban policies accordingly. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.